Exploring Ecocomposition in Latin America in the context of English Education. / Explorando la ecocomposición en América Latina en el contexto de la enseñanza del inglés. - SIGERSON, Andrew Lee (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The use of authentic materials is a fundamental factor in the teaching of English to speakers of other languages (TESOL). However, the question of the appropriateness of a given material is a complex question related to, among other factors, its relevance to the students. Thomas (2014) suggests utilizing “locally relevant authentic materials,” an idea which, in the context of composition specifically, corresponds to a recent branch of composition studies in North America known as ecocomposition, which calls for a pedagogical approach centered on students’ realities and local environments. This article explores its potential importance for TESOL in Latin America and is situated in the contemporary context of English as a language intertwined with the forces of globalization.RESUMEN El uso de materiales auténticos es un factor esencial en la enseñanza del inglés para hablantes de otras lenguas (TESOL). Sin embargo, la pertinencia de un material dado es un tema complejo relacionado, entre otros factores, con su relevancia para los estudiantes. Thomas (2014) sugiere utilizar “materiales auténticos de relevancia local”, una idea que, en el contexto específico de la redacción, correspondería a una rama reciente de la enseñanza de la escritura en norteamérica que se llama ecocomposition, la cual exige un enfoque pedagógico centrado en la realidad de los estudiantes y sus ambientes locales. Este artículo explora su potencial importancia para TESOL en América Latina y el estudio del inglés en el contexto contemporáneo en tanto lengua entrelazada con las fuerzas de la globalización.